ANALISIS FAKTOR DEMOGRAFI YANG BERHUBUNGAN DENGAN KEJADIAN HIV PADA KELOMPOK LELAKI SEKS LELAKI (LSL) DI PUSKESMAS CIPUTAT PERIODE TAHUN 2009 - 2025 (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2026)
ABSTRACTBackground: HIV/AIDS is a significant health problem, especially in the group of Men Who Have Sex with Men (MSM) who are at high risk of HIV infection. South Tangerang City, specifically Ciputat Public Health Center, has recorded a high number of HIV cases within this group. Objective: This study aims to analyze the demographic factors associated with the incidence of HIV among MSM at Ciputat Public Health Center during the period 2009-2025. Methods: This quantitative study used a retrospective cohort design with secondary data from medical records and Voluntary Counseling and Testing (VCT) services. Results: Univariate analysis used descriptive statistics and bivariate analysis used the Kendall Tau correlation test using SPSS. The population consisted of 348 MSM who visited Ciputat Public Health Center between 2009-2025, with a total sample of 344 respondents fulfilling the inclusion criteria. The majority of respondents were aged over 20 years (91,6%), had higher education (91,3%) and were employed (79,7%). The prevalence of HIV positive was 72,7%. Conclusion: Age and employment status showed significant associations with HIV incidence, whereas education level did not. Sexually Transmitted Infections (STIs) demonstrated a highly significant relationship with HIV incidence. The conclusion is that age, employment status, and STIs play significant roles in HIV incidence among MSM. Prevention programs should target older age groups and the unemployed, as well as focus on controlling STIs. Strengthening education and HIV prevention interventions at Ciputat Public Health Center, particularly for high-risk groups, is recommended.                                                     ABSTRAKLatar Belakang: HIV/AIDS merupakan masalah kesehatan signifikan khususnya pada kelompok Lelaki Seks Lelaki (LSL) yang memiliki risiko tinggi terinfeksi HIV. Kota Tangerang Selatan khususnya Puskesmas Ciputat mencatat kasus HIV yang tinggi pada kelompok ini. Tujuan: Penelitian ini bertujuan untuk menganalisis faktor demografi yang berhubungan dengan kejadian HIV pada kelompok Lelaki Seks Lelaki di Puskesmas Ciputat periode 2009-2025. Metode: Penelitian kuantitatif dengan desain kohort retrospektif menggunakan data sekunder dari rekam medis dan layanan VCT. Analisis univariat menggunakan statistik deskriptif dan analisis bivariat menggunakan uji korelasi Kendall Tau pada SPSS. Populasi sebanyak 348 LSL yang berkunjung ke Puskesmas Ciputat tahun 2009-2025, dengan sampel total 344 responden yang memenuhi kriteria inklusi. Hasil: Sebagian besar responden berusia 20 tahun (91,6%), berpendidikan lanjut (91,3%) dan bekerja (79,7%). Prevalensi HIV positif sebesar 72,7%. Usia dan pekerjaan berhubungan signifikan dengan kejadian HIV, sedangkan pendidikan tidak. Infeksi Menular Seksual (IMS) menunjukkan hubungan sangat signifikan dengan kejadian HIV. Kesimpulan: Faktor usia, pekerjaan, dan IMS berperan signifikan dalam kejadian HIV pada kelompok LSL. Program pencegahan perlu menyasar kelompok usia dewasa akhir dan yang tidak bekerja serta pengendalian IMS. Adanya penguatan edukasi dan intervensi pencegahan HIV di Puskesmas Ciputat khususnya untuk kelompok berisiko tinggi.